Tracing of travelling of stress deformation waves after the Tohoku earthquake - Kalenda, P. (Pavel); Holub, K. (Karel); Rušajová, J. (Jana); Neumann, L. (2014)
The deformation waves, which were created during the strongest earthquakes, were traced on their way around the globe. These deformation waves follow the focal mechanisms and start after the mainshocks. The deformation waves after the Chile earthquake on February 27, 2010 (M=8,8´) and the Mentawai earthquake (Indonesia) on October 25, 2010 (M=7,7) used the global tectonic structures with NW-SE orientations and they spread mostly to the west - northwest. On the other hand, two deformation waves were created after the Tohoku earthquake on March 11, 2011 (M=7,3, M=9). The first, a weaker deformation wave spread to the west from Honshu and the second travelled to the north and through the north pole to Greenland and Europe.